Young Shorty Again Vicky's House - Webster, James (Ginn and Company Ltd, 1981)
Young shorty books and more young shorty books comprise the second stage of rescue reading. the six books in shorty the puppy form the first stage and 'the rescue' in the yyoung shorty books is the immediate sequel to the sequence of stories in shorty the puppy.
Keywords: Juvenile literature-Fiction